KONFLIK PERAN, KETIDAKJELASAN PERAN, STRES KERJA, DAN KUALITAS AUDIT INSPEKTORAT PROVINSI BENGKULU - Litania, Litania (UNIB Press, 2019)
The purpose of the study is to analyze the influence of the role conflict and role ambiguity toward work stress and to analyze effect of work stress toward audit quality auditor Inspectorate in the Bengkulu Province. The data were used primary data, which obtained questionnaire to the data collecting. The sampling was used census method, equal to 167 respondents. The methods of data analysis were used Structural Equation Modeling (SEM). The result from the data analyze show that: (1) the role conflict has a positive significant influence toward work stress; (2) the role conflict has a positive significant influence toward audit quality; (3) the role ambiguity has a positive significant influence toward work stress; (4) the role ambiguity has a negative significant influence toward audit quality; (5) the work stress has negative significant influence toward audit quality; (6) the work stress has mediating effect on influence of role conflict toward the audit quality in the Inspectorates Offices in Bengkulu Province; and (7) the work stress has not mediating effect on influence of role ambiguity toward the audit quality in the Inspectorates Offices in Bengkulu Province.